Political Development through Renewable Energy: The Use of Ex-Mining Land in Indonesia’s New Capital - Elyta, Elyta; Zulkarnaen, Zulkarnaen; Zhyvko, Zinaida; Salvador Bizotto, Beatriz Lucia; As’ad, Muhammad Uhaib (SCAD Independent, 2025)
In contemporary governance, the relocation of national capital is a recurring phenomenon. This study aimed to analyze the potential for political and developmental advancement through renewable energy in Indonesia’s new archipelagic capital by repurposing former mining sites. An explanatory qualitative method was employed, using internet-based media as the primary means of reporting and online news outlets as the main data sources. The N Capture feature—a web browser plugin designed to collect online materials from websites, social media platforms, and documents such as scientific publications—was used to gather data in Nvivo 12 Plus. The findings indicate that repurposing abandoned mining sites in the archipelagic capital for renewable energy development could yield significant economic, social, and environmental benefits. However, stakeholders—including the public sector, private corporations, non-governmental organizations (NGOs), and local community—must collaborate to fully realize this potential. The use of abandoned mining lands should be strategically assessed to develop innovative solutions that address contemporary challenges while considering environmental sustainability, social equity, and economic viability.